Development of power converter sizing tool: sub-module for inductor sizing tools - Li, Shufan (2016)
This project “Development of Power Converter Sizing Tool: Sub-module for Inductor Sizing Tools” was proposed given the background that the aviation industry has a trend to design the aircraft to More Electric Aircraft (MEA) with More Electric Engine (MEE). The project focuses on the development of an “Inductor Sizing Tool” to design the inductor component within the MEE, which may serve as an important tool in the industry. Engineers come up with the concept of MEE to make aircrafts more capacious, smarter and more affordable. The MEE technology requires high-power, high-efficiency, lightweight motor and generators, as well as High Power Density Converter (HPDC) to interface with the electric-consumed elements and sections. The inductor in AC filter serves as the stabilizator of the power supply to the electric elements and sections. The power converter, and the elements including the inductor, should be designed to minimize the size at the high power density environment. In this project, the algorithm and the formulas to design an effective valid inductor with minimized size, working at the high power density environment, involving maximum current and flux density allowed, are derived. The design also takes into consideration of the margin level. After some trial to construct the Graphical User Interface GUI programs on different software, for example, the MATLAB and Mathematica, the GUI program “Inductor Sizing Tool” is developed in Visual Studio 2015 Community, to provide the potential customers the convenient and visual result of the inductor design, including the size and the power loss estimation, with given specifications. The program plots graphs on changes of weight and volume, power loss and temperature rise of the inductor design with respect of margin level. The GUI program “Inductor Sizing Tool” is integrated with the “Power Converter Sizing Tool” to provide customers the overall design and estimation of the high power density converter. On fulfilment of the GUI program, the inductor with certain design generated is constructed physically. The specifications, inductance, weight and volume are measured and verified with the result shown in GUI. Results clarify that the GUI program is valid and the program has been published to the Rolls-Royce’s customers. Some proposals of future improvement is listed in the future work part, including the continuous perfection of the inductor design mechanisms, choices of materials of inductor core, the design of GUI program with different converter topology, to make the program more powerful and competitive in the industry. More experiments and verifications can be carries out to fully examine the designs in the program. In general, this final year project provides a powerful tool for the real customers and users in the industry. Therefore it is considered to be successful.